Artificial Intelligence In Dentistry: Where Are We Now And Where Are We Heading Next? - Ahmad Badruddin Ghazali; Nur Imanina Abdullah Thaidi; Mohd Nazrin bin Mohd Isa (Universiti Sains Islam Malaysia, 2024)
3 rd INTERNATIONAL SEMINAR ON ISLAM AND SCIENCE 2020 (SAIS 2020) COVID-19: IMPLICATION, IMPACT AND SOLUTION Date: 15 October 2020 Organized by: Persatuan Kakitangan Akademik USIM (PKAUSIM) In Collaboration with: International Halal and Fatwa Centre (iFFAH) & Fakulti Syariah dan Undang-Undang (FSU)